Antibacterial and antifungal efficacy of platelet-rich fibrin and platelet-rich fibrin matrix against root canal microflora - Pinky Singh; Subhra Dey; Vinisha Pandey; Arora Abhas; Suprabha Sharan; Neetu Kharat (Wolters Kluwer Medknow Publications, 2021)
Background: Binding of such proteins with a developing fibrin mesh or to the extracellular matrix has the ability to create chemotactic gradients aiding the recruitment of stem cells, thereby, stimulating cell migration and differentiation this may promotes repair and regeneration. There is a unique concept in platelet concentrates called platelet-rich fibrin matrix (PRFM) which is processed using higher attraction without the utilization of bovine thrombin. Aim and Objectives: The aim of this study is to evaluate the antibacterial and antifungal effects of platelet-rich fibrin (PRF) and PRFM against root canal microflora. Materials and Methods: Blood samples were taken from 20 adults, age ranging from 20 to 40 years who were systemically healthy, nonsmokers with no symptoms of infection, or on antibiotics at least 3 months before experiments. The procedures and the protocols involved in the study were accepted by the Institutional Ethical Committee. Written informed consent was obtained from the donors and patients. Approximately 10 ml of blood was collected from each donor. 5 ml of blood was used for the preparation of PRF and 5 ml for PRFM. Results: The antifungal scores among the groups. The highest antifungal scores were seen in metapex followed by PRF and PRFM group. Kruskal-Wallis test was applied to check the statistical difference among the groups, and there was a statistically significant difference seen among the groups (P = 0.00). The antibacterial scores among the groups. The highest antibacterial scores were seen in Metapex followed by PRF group and PRFM group Kruskal-Wallis test was applied to check the statistical difference among the groups, and there was a statistically significant difference seen among the groups. Conclusion: PRF demonstrated antibacterial activity against passage isolates but had no antifungal efficacy. This antibacterial property may be a valuable adjunct when using PRF for regenerative procedures in endodontics. Both PRF and PRFM have to be analyzed for antimicrobial properties for extended duration and various other clinical strains with larger sample size.